SOCIAL NETWORKS AND THEIR INFLUENCE ON THE CHOICE OF RESTAURANT IN THE EXAMPLE OF THE HOSPITALITY INDUSTRY OF THE REPUBLIC OF SERBIA - Stanojević, Mateja; Kalenjuk Pivarski, Bojana; Šmugović, Stefan; Stošić, Tamara (The Business of Tourism, 2024)
Social networks were created as one of the forms of online communication of Internet users. Although many catering facilities have their own website, their presence on social networks is very important, as well as the optimization of these two channels. On social networks, catering facilities can inform potential service users about their services, discounts, organizing events, special offers, but they can also present their own photos, videos, virtual tours of catering facilities and thus contribute to the tangibility of catering services. The subject of this paper is the impact that the use of social networks has on the choice of catering facilities on the example of the hospitality and tourism industry of the Republic of Serbia and its importance for the hospitality industry. The task of this paper is to investigate the factors that determine the influence of the use of social networks on the choice of catering facilities by consumers, with the aim of determining which factors have an impact on the use of social networks and whether this affects the decision to go to a catering facility.